Floating marine debris influx in the intertidal zone of offshore islands in Bangladesh: A case study of Manpura Island - Uddin, Md. Mahin; Islam, M. Shahidul (Marine pollution bulletin, 2023)
Marine Debris is all-pervading in the world's oceans. In this research, for the first time, Floating Marine Debris (FMD) accumulation in the intertidal zone of Manprua island, an offshore island of Bangladesh, is reported. The assessment has been done by integrating both physical investigations and questionnaire survey. The Study shows high debris density on the windward and river-facing sides of the island. The density of debris items in this area varies from 550,000 to 60,000 items per km (8.5 to 0.08 g/m ) for transect samples during low tide and 350,000 to 60,000 items per km (5.76 to 1.20 g/m ) for net samples during high tide. However, the most damaging debris items are uprooted trees and water hyacinths because they hinder fishing activities. This study provides baseline information on FMD in the Meghna Estuary, which can be used as a reference for sustainable monitoring and management of marine pollution.